Análisis de la matriz de Boston de la empresa UNILEVER en la ciudad de Machala. - Agila Reyes, Vanessa Lisseth (My University, 2019)
This research is intended to analyze the Boston Matrix of the Unilever Company in Machala City. The objective is to evaluate the matrix and strategic business units such as Dove, Lux, Knorr and Sedal, in order to define strategies for these UEN and achieve the company's continuous economic growth. Orienting a qualitative analysis based on the collection of data from primary sources such as observation and interviewing techniques, and bibliographic sources such as books, articles, and the respective elaboration of the Boston matrix for the UENs, with the respective results of the research based on the determination of the position of the products in the matrix for the establishment of strategies achieving an improvement of the company at the company level.
En esta investigación se pretende analizar La Matriz De Boston de La Empresa Unilever en La Ciudad De Machala. El objetivo es evaluar la matriz y las unidades estratégicas de negocio como Dove, Lux, Knorr y Sedal, con la finalidad de definir estrategias para estas UEN y alcanzar el continuo crecimiento económico de la empresa.Orientando un análisis cualitativo en base a la recolección de datos de fuentes primarias como la técnicas de observación y entrevista además fuentes bibliográficas como libros, artículos, y la respectiva elaboración de la matriz de Boston para las UEN, con el respectivo resultado de la investigación en base a la determinación de la posición de los productos en la matriz para el establecimientos de estrategias logrando una mejora de la empresa a nivel empresarial.
Keywords: MATRIZ DE BOSTON; ESTRATEGIAS DE MARKETING; UNILEVER